1977
DOI: 10.1083/jcb.74.1.181
|View full text |Cite
|
Sign up to set email alerts
|

The structure of postsynaptic densities isolated from dog cerebral cortex: I. overall morphology and protein composition

Abstract: A postsynaptic density (PSD) fraction, including some adherent subsynaptic web material, has been isolated from dog cerebral cortex by a short-procedure modification of the methods of Davis and Bloom (21,22) and Cotman and Taylor (20), using Triton X-100. The fraction has been visualized by thin-section, replica, and negative (phosphotungstic acid) staining electron microscopy and its proteins separated by high-resolution SDS gel electrophoresis. Morphologically, the preparation seems to be quite pure, with ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
367
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 477 publications
(392 citation statements)
references
References 61 publications
25
367
0
Order By: Relevance
“…The presence of brevican in this fraction has already been reported (Seidenbecher et al 1998;Niederöst et al 1999) and it was suggested to contribute to the nonpermissive properties of CNS myelin (Niederöst et al 1999). The light membrane fraction is a less well defined membrane subpopulation, which contains a mixture of endoplasmic reticulum, Golgi and plasma membranes as estimated by electron microscopy (Cohen et al 1977;Hu et al 1998). This fraction contains extrasynaptic marker molecules of neuronal membranes, such as BDNF receptor gp145trkB and gp95trkB or the 5-hydroxytryptamine receptor 2A (Hu et al (b) (a) Fig.…”
Section: Discussionmentioning
confidence: 83%
“…The presence of brevican in this fraction has already been reported (Seidenbecher et al 1998;Niederöst et al 1999) and it was suggested to contribute to the nonpermissive properties of CNS myelin (Niederöst et al 1999). The light membrane fraction is a less well defined membrane subpopulation, which contains a mixture of endoplasmic reticulum, Golgi and plasma membranes as estimated by electron microscopy (Cohen et al 1977;Hu et al 1998). This fraction contains extrasynaptic marker molecules of neuronal membranes, such as BDNF receptor gp145trkB and gp95trkB or the 5-hydroxytryptamine receptor 2A (Hu et al (b) (a) Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Disc-shaped, segmented and perforated PSDs, consisting of granular and filamentous materials, have been observed by electron microscopy (Cohen and Siekevitz 1978;Spack 1985;Harris and Stevens 1989;Peters et al 1991;Geinisman et al 1992;Itarat and Jones 1993). Biochemical procedures have been developed to isolate PSDs from the brains of different animals (Cotman et al 1974;Cohen et al 1977;Gurd et al 1982). The isolated PSDs appeared to retain the morphological characteristics of their brain counterparts.…”
mentioning
confidence: 99%
“…Column chromatography was performed in the cold on a Sepharose CL-4B column (1.6 x 100 cm) (Pharmacia, Uppsala, Sweden Neville (1971) as modified by Cohen et al (1977). The gels were stained with Coomassie Brilliant Blue R (Sigma) and destained as described by Chua & Bennoun (1975).…”
mentioning
confidence: 99%
“…The gels were stained with Coomassie Brilliant Blue R (Sigma) and destained as described by Chua & Bennoun (1975). Human IgG and IgM, o-actinin, dog-brain neurofilament protein and post-synaptic density proteins (Cohen et al, 1977) were used as mol.-wt standards.…”
mentioning
confidence: 99%